1997
DOI: 10.1063/1.120206
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency and high-resolution fiber-optic probes for near field imaging and spectroscopy

Abstract: Articles you may be interested inInstrumentation for dual-probe scanning near-field optical microscopy Rev. Sci. Instrum. 83, 083709 (2012); 10.1063/1.4737883 Simple fiber-optic confocal microscopy with nanoscale depth resolution beyond the diffraction barrier Rev. Sci. Instrum. 78, 093703 (2007); 10.1063/1.2777173 Fiber-optic coupled probe for scanning optically active materials Rev. Sci. Instrum. 69, 4234 (1998); 10.1063/1.1149236Highly efficient excitation of optical near-field on an apertured fiber probe w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Also, nanoscale changes in surface morphology are best tracked when the probe has a sharply pointed tip, and a smooth taper assists in the prevention of light leakage from the probe. Several methods have been used to prepare sharply tapered NSOM probes for optical spectroscopy, including chemical etching (18 -21, 44-46), focused ion beam milling (47), heat-pulling (15,16), micromachining (48,49), and hybrid heat-pulling/chemical etching combinations (50). Only two methods, namely heat-pulling (33,34) and chemical etching (27 -29, 32, 37, 41), have been specified in the literature as methods for fabricating apertured probes for near-field laser ablation, and these methods are described in the following paragraphs.…”
Section: Fabrication Of Near-field Scanning Optical Microscopy Probesmentioning
confidence: 99%
“…Also, nanoscale changes in surface morphology are best tracked when the probe has a sharply pointed tip, and a smooth taper assists in the prevention of light leakage from the probe. Several methods have been used to prepare sharply tapered NSOM probes for optical spectroscopy, including chemical etching (18 -21, 44-46), focused ion beam milling (47), heat-pulling (15,16), micromachining (48,49), and hybrid heat-pulling/chemical etching combinations (50). Only two methods, namely heat-pulling (33,34) and chemical etching (27 -29, 32, 37, 41), have been specified in the literature as methods for fabricating apertured probes for near-field laser ablation, and these methods are described in the following paragraphs.…”
Section: Fabrication Of Near-field Scanning Optical Microscopy Probesmentioning
confidence: 99%
“…Possible uses of nanosized biomolecules or composites are in magnetic recording (when combined with magnetic nanoclusters; Mayes et al 2003), molecular-scale spintronics (magnetic switches) (Ruben et al 2003), coupling of nanodevices with optical signals [already shown for virions (Dragnea et al 2003;Islam et al 1997)], and molecular-scale electronic switches (Keren et al 2003). For extreme cases, quantum mechanics plays a huge role, e.g.…”
Section: Outlinementioning
confidence: 99%
“…The interest in knowing the exact behavior of fields at the end of the fiber has increased due to the widespread applications of the optical fiber in various systems. Studying the diffraction from fiber ends is also important for integrated optics applications, interferometric sensors and near-field fiber probes [3].…”
Section: Introductionmentioning
confidence: 99%